myExperiment: A repository and social network for the sharing of bioinformatics workflows - Goble, C; Bhagat, J; Aleksejevs, S; Cruickshank, D; Michaelides, D; Newman, D; Borkum, M; Bechhofer, S; Roos, M; Li, P; de Roure, D (2010)
myExperiment (http://www.myexperiment.org) is an online research environment that supports the social sharing of bioinformatics workflows. These workflows are procedures consisting of a series of computational tasks using web services, which may be performed on data from its retrieval, integration and analysis, to the visualization of the results. As a public repository of workflows, myExperiment allows anybody to discover those that are relevant to their research, which can then be reused and repurposed to their specific requirements. Conversely, developers can submit their workflows to myExperiment and enable them to be shared in a secure manner. Since its release in 2007, myExperiment currently has over 3500 registered users and contains more than 1000 workflows. The social aspect to the sharing of these workflows is facilitated by registered users forming virtual communities bound together by a common interest or research project. Contributors of workflows can build their reputation within these communities by receiving feedback and credit from individuals who reuse their work. Further documentation about myExperiment including its REST web service is available from http://wiki.myexp eriment.org. Feedback and requests for support can be sent to bugs@myexperiment.org. © The Author(s) 2010. Published by Oxford University Press.